Added value of umbilical vein flow as a predictor of perinatal outcome in term small‐for‐gestational‐age fetuses. (26th July 2013) - Parra‐Saavedra, M.; Crovetto, F.; Triunfo, S.; Savchev, S.; Parra, G.; Sanz, M.; Gratacos, E.; Figueras, F.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2013:42:130 ABSTRACT: Objective: To compare umbilical vein (UV) flow with standard Doppler parameters in prediction of adverse perinatal outcome in late‐onset small‐for‐gestational age (SGA) fetuses. Methods: Umbilical, uterine and middle cerebral arteries, and UV blood flow were evaluated by Doppler before delivery in a cohort of 193 term SGA fetuses. The value of the Doppler parameters to predict risk of emergency delivery for non‐reassuring fetal status and neonatal metabolic acidosis was analyzed. Results: Fifty‐three (27%) fetuses had non‐reassuring fetal status requiring emergency delivery, whereas 21 (11%) newborns developed neonatal metabolic acidosis. Multivariable analysis showed that significant contributions to prediction of emergency delivery for non‐reassuring fetal status and neonatal metabolic acidosis were provided by middle cerebral artery (MCA) pulsatility index (PI) and UV blood flow normalized by fetal weight. Decision tree analysis defined three groups with increasing risk of need for emergency delivery for non‐reassuring fetal status: MCA‐PI > 1.46 (risk 15.6%); MCA‐PI ≤ 1.46 and UV blood flow > 68 mL/min/kg (risk 25%); and MCA‐PI ≤ 1.46 and UV flow ≤ 68 mL/min/kg (risk 53.1%); and two groups with different risks of neonatal metabolic acidosis: UV flow > 68 mL/min/kg or UV flow ≤ 68 mL/min/kg and MCA‐PI > 1.23 (risk ≤ 10%); and UV flow ≤ 68 mL/min/kg and MCA‐PI ≤ 1.23 (risk 39.1%). Conclusion: The evaluation of UV blood flow with spectral brain Doppler allows better identification of SGA fetuses with late‐onset intrauterine growth restriction at risk of adverse perinatal outcome. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.